Optimization of electron beam irradiation and ionic liquid pretreatment on oil palm trunk: article - Meor Harun, Wan Azizah; Azizan, Amizon (2019)
Oil palm trunk (OPT) waste from the oil palm plantation is one of the lignocellulosic biomass feedstock to produce biofuel. Pretreatment is an important process to break the rigid structure of the lignocellulose and make it accessible for hydrolysis. In this project, the OPT was pretreated by using electron beam irradiation and ionic liquid. The effectiveness of the pretreatment process was investigated by analyzing the crystallinity index (CrI) of the pretreated OPT by using X-Ray Diffractometer (XRD). The optimal conditions for the pretreatment process were determined by response surface methodology with Box-Behnken Design for the experimental design. The result shows that the optimal conditions for the pretreatment process can be obtained at 346.5 kGy of irradiation dose, 686.9 rpm of shaking frequency and 3 hours of dissolution time. The predicted CrI value at the optimal conditions is 32.82%.